2000
DOI: 10.1128/iai.68.6.3368-3376.2000
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Organization and Function of Invasion Genes within Salmonella enterica Serovar Typhimurium Pathogenicity Island 1, Including the prgH , prgI , prgJ , prgK , orgA , orgB , and orgC Genes

Abstract: Salmonella enterica serovar Typhimurium initiates infection of a host by inducing its own uptake into specialized M cells which reside within the epithelium overlaying Peyer's patches. Entry of Salmonella into intestinal epithelial cells is dependent upon invasion genes that are clustered together in Salmonella pathogenicity island 1 (SPI-1). Upon contact between serovar Typhimurium and epithelial cells targeted for bacterial internalization, bacterial proteins are injected into the host cell through a type II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
61
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 45 publications
(56 reference statements)
3
61
1
Order By: Relevance
“…The HilC and HilD proteins repressed the upstream promoter, which uses an extended ÏȘ10 element at positions ÏȘ88 to ÏȘ80, and activate the silent downstream promoter. Reverse transcriptase PCR analysis suggested that hilC is also transcribed from even farther upstream (21). These results indicate that HilC and HilD can function as direct transcription activators at the hilC promoter, unlike their proposed role at the hilA promoter to relieve repression.…”
Section: Discussionmentioning
confidence: 72%
“…The HilC and HilD proteins repressed the upstream promoter, which uses an extended ÏȘ10 element at positions ÏȘ88 to ÏȘ80, and activate the silent downstream promoter. Reverse transcriptase PCR analysis suggested that hilC is also transcribed from even farther upstream (21). These results indicate that HilC and HilD can function as direct transcription activators at the hilC promoter, unlike their proposed role at the hilA promoter to relieve repression.…”
Section: Discussionmentioning
confidence: 72%
“…The 2-kb DNA product was cloned into pGEM-T Easy (Promega, Madison, WI) and a blunt-ended aphT gene encoding kanamycin resistance was ligated into the middle of the sseD gene digested with EcoRV. The sseD-aphT construct was cloned into the pBDJ129 vector, followed by selection for allelic exchange of the mutated sseD into the SL1344 chromosome (18,19). This strain was designated S. typhimurium JK22.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
“…The core of the complex, probably found embedded in the inner membrane and crossing the periplasmic space, is comprised of PrgH and PrgK, while the barrel of the syringe is predominantly PrgI, a protein that requires PrgJ for its stability (20). The genes encoding these proteins are in an operon (prgHIJK-orgABC) at one end of SPI1 (20)(21)(22)(23) (Fig. 1A).…”
mentioning
confidence: 99%